Implementasi model project based learning untuk meningkatkan hasil belajar IPAS di kelas IV di sekolah dasar - Arum Nugrahani; Jenny Indrastoeti Siti Poerwanti; Chumdari Chumdari (Jurnal Pendidikan Dasar, 2025)
Abstract. This study aims to describe with the implementation of the project-based learning model in improving the learning outcomes of science and science in grade IV in elementary school. The research subjects consisted of 11 female students and 5 male students along with grade IV teachers in elementary schools. Data collection techniques with written tests of cognitive multiple-choice questions (summative assessment at the end of learning), observation (learning activities), documentation (photos of evidence of learning activities in the implementation of PTK), and interviews (in-depth interviews with teachers and students). Data analysis techniques by combining quantitative and qualitative approaches. The interactive data analysis technique consists of data reduction, data presentation, conclusion drawing and verification. The results of the study show that the learning outcomes of social studies in grade IV in elementary schools can be improved by the implementation of the project-based learning model. Research data shows that there is an increase of 44%, from the initial 44% to 88%. The science and technology subject matter used for research is about local wisdom.